PEMBELAJARAN INKUIRI TERBIMBING DENGAN MENERAPKAN NILAI-NILAI KARAKTER KONSERVASI UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN KETERAMPILAN KERJA ILMIAH SISWA SMA (UPEJ Unnes Physics Education Journal, 2015)
This research aims to know the effectiveness of increase the concept comprehension and scientific work skill of senior high school students by applying conservation character values. Based on the data analysis normalized gain test <g>, there is improvement of concept comprehension in experimental group with score 0,56 and 0,48 in control group which both scores are on medium level. It tells the improvement of concept comprehension in experimental group is higher than control group. The value <g> of scientific work skill in each group is 0,43 and 0,31. This research gives the conclution that guided inquiry learning by applying the conservation character values is effective to increase the concept comprehension and scientific work skill of senior high school students.